2010
DOI: 10.1016/j.chemosphere.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structure and a secondary carbon source on the microbial degradation of chlorophenoxy acids

Abstract: a b s t r a c tPseudomonas putida, Aspergillus niger, Bacillus subtilis, Pseudomonas flourescens, Sphingomonas herbicidovorans and Rhodococcus rhodochrous growing on glucose in a medium containing one of three chlorophenoxy acids at a concentration of 0.1 g L À1 (clofibric acid, (R)-2-(4-chloro-2-methylphenoxy)propionic acid (mecoprop or MCPP) and 4-chloro-2-methylphenoxyacetic acid (MCPA)) degraded these compounds to varying degrees; from nonmeasurable to almost complete removal. These results with the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…However, CLF removal was still not observed after another 2 months of SBR operation (data not shown). These results show that not all activated sludge communities have the capacity to degrade CLF, which explains the contradictory biodegradation efficiencies observed in different WWTPs [9,11,12]. This motivated the use of a microbial community already adapted to chlorinated ring-based compounds.…”
Section: Clofibric Acid Biotransformationmentioning
confidence: 69%
See 2 more Smart Citations
“…However, CLF removal was still not observed after another 2 months of SBR operation (data not shown). These results show that not all activated sludge communities have the capacity to degrade CLF, which explains the contradictory biodegradation efficiencies observed in different WWTPs [9,11,12]. This motivated the use of a microbial community already adapted to chlorinated ring-based compounds.…”
Section: Clofibric Acid Biotransformationmentioning
confidence: 69%
“…While Evangelista et al [12] found that >90% of a 100 mg L −1 CLF solution was transformed by Rhodococcus rhodochrous in 20 days after acclimatisation, it was mainly transformed into its parent compound ethyl clofibrate, which accumulated in the solution. Winkler et al [2] found that CLF was not removed at an initial concentration of 90 g L −1 (over ∼400 h) and only 27% removal was obtained at 11 g L −1 (over ∼95 h) in a biofilm reactor fed with river water.…”
Section: Nitrification Inhibitionmentioning
confidence: 96%
See 1 more Smart Citation
“…The biodegradation result is thus derived exclusively from oxidation of the propionate part of the side chain. The combination of an ether function with a tetra‐substituted carbon containing a geminal dimethyl attached to it was previously concluded as difficult to degrade in the case of chlorophenoxy acids .…”
Section: Resultsmentioning
confidence: 99%
“…The maximum removal yield achieved was 51% for an initial CLA concentration of 2 mgL -1 . Furthermore, Evangelista et al (2010) studied the biodegradation of three chlorophenoxy acids using axenic cultures of bacteria under cometabolic conditions. Nevertheless, none of the tested microorganisms was able to degrade clofibric acid suggesting that the recalcitrance of clofibric acid is due to the additional methyl group adjacent to the ether bond (2010).…”
Section: Introductionmentioning
confidence: 99%